Tannin extract from maritime pine bark exhibits anticancer properties by targeting the epigenetic UHRF1/DNMT1 tandem leading to the re-expression of TP73. Issue 1 (13th December 2021) - Ashraf, Waseem; Ahmad, Tanveer; Almalki, Naif A. R.; Krifa, Mounira; Zaayter, Liliyana; Pizzi, Antonio; Muller, Christian D.; Hamiche, Ali; Mély, Yves; Bronner, Christian; Mousli, Marc
Abstract : Maritime pine bark is a rich source of polyphenolic compounds and is commonly employed as a herbal supplement worldwide. Abstract : Maritime pine bark is a rich source of polyphenolic compounds and is commonly employed as a herbal supplement worldwide. This study was designed to check the potential of maritime pine tannin extract (MPTE) in anticancer therapy and to determine the underlying mechanism of action. Our results showed that MPTE, containing procyanidin oligomers and lanostane type terpenoids, has an inhibitory effect on cancer cell proliferation through cell cycle arrest in the G2/M phase. Treatment with MPTE also induced apoptosis in a concentration-dependent manner in human cancer cell lines (HeLa and U2OS), as evidenced by the enhanced activation of caspase 3 and the cleavage of PARP along with the downregulation of the antiapoptotic protein Bcl-2. Interestingly, human non-cancerous fibroblasts are much less sensitive to MPTE, suggesting that it preferentially targets cancer cells. MPTE played a pro-oxidant role in cancer cells and promoted the expression of the p73 tumor suppressor gene in p53-deficient cells. It also downregulated the protooncogenic proteins UHRF1 and DNMT1, mediators of the DNA methylation machinery, and reduced the global methylation levels in HeLa cells. Overall, our results show that maritime pine tannin extract can play a favorable role in cancer treatment, and can be further explored by the pharmaceutical industry.